Peran Teknologi Blockchain dalam Meningkatkan Transparansi dan Efisiensi Transaksi Business-to-Business (B2B): Systematic Literature Review - Nurhaeni Sikki; Meyustina Noviantika Sitohang; Karina Agusta Putri; Megawati Sitohang; Juliyanti Harar (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study examines the role of blockchain technology in building digital trust and increasing the transparency and efficiency of Business-to-Business (B2B) transactions through a Systematic Literature Review (SLR) approach. A literature search was conducted in the Scopus database, referring to PRISMA guidelines, and limited to English-language journal articles relevant to the B2B context. Descriptive and thematic analyses were used to map publication trends, research distribution, and study focus. The results indicate that blockchain is positioned as a B2B transaction infrastructure based on immutable ledgers, smart contracts, and cross-organizational interoperability. Despite its widely recognized potential, the literature is still dominated by conceptual and sectoral studies, with limited empirical evidence across industries and challenges of scalability and regulation.